STRATEGI KOLABORATIF BERBASIS MASALAH DALAM PENGELOLAAN BATAS WILAYAH KELURAHAN BANGKA BELITUNG DARAT KOTA PONTIANAK DENGAN DESA SUNGAI RAYA DALAM KABUPATEN KUBU RAYA - Zulkarnaen Zulkarnaen; Joko Triyono; Ahirul Habib Padilah (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2023)
ABSTRACT The condition of the ditch/river in the Raya Dalam River as the boundary between the Bangka Belitung Darat Sub-district, Pontianak City and Sungai Raya Dalam Village looks dirty and shabby, people still find people throwing garbage out of place, there are street vendors who are not orderly, traffic jams traffic caused by vehicle parking on the shoulder of the road and traffic chaos, and damaged road infrastructure sometimes disrupt access for the local community and road users. This type of research is descriptive qualitative. Data collection techniques using interviews, observation, and documentation. The results of the study show that in managing the border area between the Bangka Belitung Darat Village and Sungai Raya Dalam Village, face-to-face dialogue has been carried out involving all stakeholders through communication, dialogue builds trust. Moving on from the trust of stakeholders, they are committed to a collaborative process in the management of boundary areas that creates a shared understanding. If the temporary results provide benefits to various parties, it is hoped that the collaboration in the management of regional boundary areas can be successful in a sustainable manner. The recommended collaborative strategy is to realize the direction of formal cooperation by increasing coordinating relationships and full cooperation in the management of regional boundaries where the two different regions are brought together to have cultural similarities. Therefore, a collaborative strategy is built using a cultural strategy to change the behavior, feelings, and way of thinking of stakeholders to change the culture that can block the direction of a change. Keywords: Management of Territory Boundaries,Collaborative Governance, Collaborative Strategy